Detailed area plan (DAP) 2022–2035 for Dhaka: The quest for identity - Chisty, Hisham Uddin; Aktar, Mahfuja (Journal of Bangladesh Institute of Planners, 2022)
Abstract not available JBIP, Vol. 15, 2022, pp. 63-69